دور المراجعة الداخلية في تحسين جودة المعلومات المحاسبية (دراسة حالة: الشركة الأهلية للإسمنت المساهمة) (Economic studies journal, 2018)
This study aimed to identify the role of internal audit in improving the quality of accounting information، And to achieve the objectives of the study، the study followed descriptive analytical method، the researchers developed a questionnaire based on some previous studies، the study population represents all internal auditors at cement Al-Ahlya company in khoums city، totalling(21) auditors، After the distribution of the questionnaire (21)forms were retrieved and valid for statistical analysis، and the analysis of the study data was done by computerized and use statistical program of service software contained in the (SPSS). It reached many results that can be summarized as follows: the study revealed that the role of internal auditing among in cment Al-Ahly company under study is actively work to improve the accounting information on financial statements. Finally the study provided a set of recommendations which will hopefully be followed to enhance and strengthen the role of internal audit in improving the quality of accounting information in cment Al-Ahly company.
Keywords: : المراجعة الداخلية; جودة المعلومات المحاسبية; كفاءة المراجع الداخلي